NGMASTER: in silico multi-antigen sequence typing for Neisseria gonorrhoeae. Issue 8 (25th August 2016) - Kwong, Jason C.; Gonçalves da Silva, Anders; Dyet, Kristin; Williamson, Deborah A.; Stinear, Timothy P.; Howden, Benjamin P.; Seemann, Torsten
Abstract : Whole-genome sequencing (WGS) provides the highest resolution analysis for comparison of bacterial isolates in public health microbiology. However, although increasingly being used routinely for some pathogens such as Listeria monocytogenes and Salmonella enterica, the use of WGS is still limited for other organisms, such as Neisseria gonorrhoeae . Multi-antigen sequence typing (NG-MAST) is the most widely performed typing method for epidemiological surveillance of gonorrhoea. Here, we present NGMASTER, a command-line software tool for performing in silico NG-MAST on assembled genome data. NGMASTER rapidly and accurately determined the NG-MAST of 630 assembled genomes, facilitating comparisons between WGS and previously published gonorrhoea epidemiological studies. The source code and user documentation are available athttps://github.com/MDU-PHL/ngmaster.